Burkitt Lymphoma of Oral Cavity in Myanmar - Win Myat Oo; Aung Aung; Nyein Chan Aung (Asian Journal of Medicine & Health Sciences, 2024)
Burkitt lymphoma is a highly aggressive but curable lymphoma, composed of monomorphic medium sized B cells with basophilic cytoplasm and numerous mitotic figures. It has endemic, sporadic, and human immunodeficiency-associated subtypes. The African or endemic variants frequently involves the maxilla and other facial bones, while head and neck manifestations in sporadic Burkitt lymphoma are rare. We present the case of a 41-year-old woman with a rapidly growing buccal mucosal growth, leading to swallowing difficulties within one month. There was no palpable lymphadenopathy or organomegaly. Serology tests for HBs antigen, HCV antibody, and HIV antibody were negative. The histological section of the biopsy tissue from the buccal mucosal growth showed infiltrating diffuse sheets of neoplastic cells. These cells appeared as monotonous, medium-sized lymphoid cells, displaying numerous apoptotic bodies and numerous tangible body macrophages, indicative of a high proliferation rate. Immunohistochemical staining of the tumor cells revealed positivity for CD20, CD10, BCL6, and CMYC, while BCL2 was negative. Additionally, the Ki67 proliferation index was exceptionally high, nearly 100%, consistent with Burkitt Lymphoma. The true incidence of Burkitt lymphoma in Myanmar is unknown due to a lack of reported cases. This underscores the importance of early diagnosis and immediate, appropriate management of the disease. The definitive diagnosis was confirmed through a meticulous histopathological examination combined with immunohistochemistry.